2021
DOI: 10.1136/thoraxjnl-2021-217299
|View full text |Cite
|
Sign up to set email alerts
|

Higher exhaled nitric oxide at 6 weeks of age is associated with less bronchiolitis and wheeze in the first 12 months of age

Abstract: BackgroundNitric oxide in exhaled air (eNO) is used as a marker of type 2 immune response-induced airway inflammation. We aimed to investigate the association between eNO and bronchiolitis incidence and respiratory symptoms in infancy, and its correlation with eosinophil protein X (EPX).MethodsWe followed up infants at 6 weeks of age born to mothers with asthma in pregnancy and measured eNO during natural sleep using a rapid response chemiluminescense analyser (CLD88; EcoMedics), collecting at least 100 breath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…In addition to asthma, elevated eNO has been reported in other inflammatory disorders in infants: established bronchopulmonary dysplasia [7], eczema [8] and airway hyperresponsiveness in infants with recurrent lower respiratory tract symptoms [9]. Contrasting this, we have recently shown that lower eNO at six weeks of age is associated with higher rates of bronchiolitis and wheeze in the first year of life [10], and decreased eNO has been described in infants with cystic fibrosis [11], respiratory syncytial virus bronchiolitis [12], wheezy bronchitis [13], and rhinorrhoea [14] making the role of eNO in respiratory disorders manifesting in early life more cryptic.…”
Section: Introductionmentioning
confidence: 67%
“…In addition to asthma, elevated eNO has been reported in other inflammatory disorders in infants: established bronchopulmonary dysplasia [7], eczema [8] and airway hyperresponsiveness in infants with recurrent lower respiratory tract symptoms [9]. Contrasting this, we have recently shown that lower eNO at six weeks of age is associated with higher rates of bronchiolitis and wheeze in the first year of life [10], and decreased eNO has been described in infants with cystic fibrosis [11], respiratory syncytial virus bronchiolitis [12], wheezy bronchitis [13], and rhinorrhoea [14] making the role of eNO in respiratory disorders manifesting in early life more cryptic.…”
Section: Introductionmentioning
confidence: 67%
“…Infant assessments and measurements including abdominal and head circumference, middle upper arm circumference, length, weight and body composition (measured by the CosMed Peapod unit)34 will be undertaken on the postnatal ward of the hospital and at HMRI during the 6-week and 6-month postpartum appointments. A subgroup of infants will receive infant lung function testing at 6 weeks postpartum, using previously published protocols 35–37…”
Section: Methodsmentioning
confidence: 99%
“…A subgroup of infants will receive infant lung function testing at 6 weeks postpartum, using previously published protocols. [35][36][37] Questionnaires A link to online questionnaires will be emailed to participants at 14, 20, 28 and 36 weeks antenatally and 6 weeks and 6 months postnatally. Questionnaires will be 'open' for 2 weeks at each timepoint and participants will be able to save and return to the questionnaires if they cannot complete them in one sitting.…”
Section: Physical Assessmentsmentioning
confidence: 99%